Foreign Direct Investment, Labour Market Regulation and Self-Interested Governments - Tapio Palokangas (Institute for the Study of Labor (IZA), 2003)
This document examines foreign direct investment (FDI) when multinationals and labour unions bargain over labour contracts and lobby the self-interested government for taxation and labour market regulation. We demonstrate that right-to-manage bargaining predicts higher returns for FDI than does non-unionization or efficient bargaining. This advantage is further magnified in the presence of credible wage contracts. When the labour market is nonunionized, or there is a bargain over employment, the ruling elite reaps the surplus of FDI through taxation or regulation. In the absence of credible contracts, unions have incentives to claim a bigger share of the revenue of FDI.
Keywords: D78; J51; F23; F21; 330; foreign direct investment; labour market regulation; lobbying; Direktinvestition; Investitionsrisiko; Multinationales Unternehmen; Gewerkschaftlicher Organisationsgrad; Lohnverhandlungstheorie; Interessenpolitik; Arbeitsmarktflexibilisierung; Standortfaktor; Theorie